Reaction material frame capable of periodically changing spreading thickness and application of reaction material frame in preparation of alpha-phase silicon nitride ceramic powder

By designing a reaction material frame that periodically changes the thickness of the laying material, the problems of local overheating and uneven heat dissipation when preparing α-phase silicon nitride ceramic powder in the prior art are solved, and the efficient preparation of α-phase silicon nitride ceramic powder is achieved, with improved yield and simple operation.

CN119524733APending Publication Date: 2025-02-28TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311116940.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art has problems of local overheating, uneven heat dissipation and low yield of α-phase in the preparation of α-phase silicon nitride ceramic powders, and the operation steps are complicated and require precise control.

Method used

A reaction material frame that periodically changes the thickness of the laying material is designed, and the heat dissipation efficiency of the reaction material is improved by designing a cyclic shape on the substrate, such as wave shape and zigzag shape, and prepared by a self-propagation combustion synthesis process.

Benefits of technology

By improving the heat dissipation efficiency of the reaction material, the local overheating phenomenon is reduced, the yield of α-phase silicon nitride is improved, and the operation is simple and control is simple, and the α-phase content is greater than 80 wt%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524733A_ABST
    Figure CN119524733A_ABST
Patent Text Reader

Abstract

The invention discloses a reaction material frame capable of periodically changing the spreading thickness and application of the reaction material frame in preparation of alpha-phase silicon nitride ceramic powder. The reaction material frame comprises an upper structural body and a lower structural body; the upper structural body and the lower structural body are integrally formed; wherein the lower structural body of the reaction material frame is a substrate with a periodic shape change. The reaction material frame is used in a conventional process for synthesizing alpha-phase silicon nitride ceramic powder through self-propagating combustion, and due to the special substrate appearance, the spreading thickness is periodically changed, and the contact area between a reaction material and the reaction material frame is increased, so that the preparation process of the alpha-phase silicon nitride ceramic powder can be simplified under the conditions of not additionally adding other materials and changing a traditional process route. The problems of local overheating and non-uniform heat dissipation in the reaction process are solved, so that the alpha-phase content is increased, and the silicon nitride ceramic powder with high alpha-phase content is synthesized. In addition, the preparation method is simple and convenient to operate, easy to adjust, high in yield and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of α-phase silicon nitride synthesis, and more specifically to a reaction material frame for periodically changing the thickness of the material and its application in preparing α-phase silicon nitride ceramic powder. Background Art

[0002] Silicon Nitride (Si 3 N 4 ) ceramics have excellent oxidation resistance, good high temperature stability, chemical stability, high strength and hardness and self-lubricating properties, and are widely used in petrochemical, steel metallurgy, automobile engines, aerospace, 5G, cutting tools, etc. Silicon nitride (Si 3 N 4 ) can be divided into α-phase silicon nitride, β-phase silicon nitride and γ-phase silicon nitride according to different phases, among which α-phase silicon nitride and β-phase silicon nitride are more common. α-phase silicon nitride is better than β-phase silicon nitride in sintering performance, so it is widely used as the main raw material for high-performance silicon nitride ceramics.

[0003] At present, the cost of synthesizing silicon nitride ceramic powder has been very high, resulting in the high cost of silicon nitride ceramics, which seriously limits its wide application in the engineering field and the full play of its excellent performance. The self-propagating high-temperature synthesis method has the advantages of low cost, fast reaction rate, high sintering activity, etc., and has gradually become the first choice for preparing silicon nitride powder. However, there is a problem that the yield of β-phase silicon nitride is high and the yield of α-phase silicon nitride is low. For this reason, Li Jinfu et al. invented a "self-propagating pollution-free and rapid method for preparing high α-phase silicon nitride ceramic powder". Although the reaction temperature is reduced and a high content of α-phase silicon nitride is obtained, the introduced additives will produce harmful substances during the reaction, causing certain damage to the surrounding environment. CN110256084B adopts a two-step reaction method (combination of silicon powder direct nitridation method and self-propagating process) to prepare α-phase silicon nitride ceramic powder, thereby controlling the reaction speed, allowing a part of the silicon powder to react first, and then at a relatively low temperature, allowing the unreacted silicon powder to continue to react, which can prevent overheating and local overheating of the reaction, reduce the reaction temperature, and help to improve the yield of α-phase silicon nitride. However, the operation steps are relatively complicated, the two-step reaction conditions need to be precisely controlled, and the switching of the two-step reaction processes also needs to be controlled, otherwise it will be difficult to achieve the expected effect.

[0004] Based on this, there is an urgent need to develop a method for preparing α-phase silicon nitride that is simple to operate, simple to control, highly feasible, and has a high α-phase yield. Summary of the invention

[0005] Based on the above defects, the first purpose of the present invention is to provide a reaction material frame with periodically changing material thickness. The reaction material frame has a special shape design in the substrate part, which is changed from the traditional flat bottom design to a shape with periodic shape changes. Through these regular convex designs, the material thickness of the reaction material can be periodically changed, which improves the problem of uneven heat dissipation of the reaction material during the combustion process and improves the heat dissipation efficiency of the reaction material.

[0006] The second object of the present invention is to provide a method for preparing α-phase silicon nitride ceramic powder using the above-mentioned reaction frame. The method adopts the traditional self-propagating combustion synthesis process and uses a self-developed reaction frame to carry the reaction materials to achieve efficient output of α-phase silicon nitride ceramic powder.

[0007] The third object of the present invention is to provide an α-phase silicon nitride ceramic powder prepared by the preparation method as described above.

[0008] In order to achieve the above first object, the present invention adopts the following technical scheme:

[0009] The present invention discloses a reaction material frame for periodically changing the thickness of a paving material, the reaction material frame comprising an upper structure and a lower structure; the upper structure and the lower structure are integrally formed;

[0010] Wherein, the lower structure of the reaction material frame is a substrate whose outer shape changes periodically.

[0011] In view of a series of problems that are prone to occur when preparing α-phase silicon nitride ceramic powder by self-propagating combustion synthesis in the prior art, such as local overheating, uneven heat dissipation, and low α-phase yield, the present invention designs a reaction material frame applied to the self-propagating combustion synthesis process. The reaction material frame increases the contact area between the reaction material and the reaction material frame during material laying by designing the substrate to have a periodic shape change, improves the heat dissipation efficiency of the reaction material, makes the heat dissipation of the material more uniform, reduces the problem of local overheating, and at the same time ensures the uniformity of the synthesized material at different positions to obtain higher α-phase silicon nitride.

[0012] Furthermore, in the design of the substrate shape, considering that there are many uncontrollable factors in non-periodic changes, which may cause uncontrollable temperature or even termination of the reaction during the reaction, as well as potential non-uniformity of the synthesized material, the present invention uses a substrate with a periodic shape change, and the shape of the substrate includes but is not limited to one or both of a wave shape and a sawtooth shape. The regular protrusions formed by the wave shape and the sawtooth shape are conducive to dispersing the reaction material and improving its heat dissipation efficiency.

[0013] Furthermore, when the substrate has a wavy shape, each circulation unit is in the shape of a hemisphere or a semi-ellipsoid of the same size, the wavelength of each wavy circulation unit is 2-5 cm, the peak height of each wavy circulation unit is 1-3 cm; the vertical distance between the peak and the upper structure is 5-7 cm, preferably 6 cm.

[0014] Furthermore, when the substrate has a sawtooth shape, each circulation unit is shaped like an isosceles triangle of the same size, the base length of each sawtooth circulation unit is 2-5 cm, and the maximum height of each sawtooth circulation unit is 1-3 cm; the vertical distance between each circulation unit and the upper structure at its maximum height is 5-7 cm, preferably 6 cm.

[0015] Furthermore, the upper structure of the reaction material frame adopts a conventional reaction material frame design, such as a rectangular parallelepiped frame with a lower opening, which can be integrally formed with the lower structure to form a carrying space for the reaction material.

[0016] Furthermore, the material of the reaction frame includes but is not limited to stainless steel or graphite.

[0017] In order to achieve the above second purpose, the present invention adopts the following technical solutions:

[0018] The invention discloses a method for preparing α-phase silicon nitride ceramic powder. The α-phase silicon nitride ceramic powder is prepared by using the reaction material frame as described above and adopting a self-propagating combustion synthesis method.

[0019] Furthermore, the present invention adopts a traditional self-propagating combustion synthesis process, and the preparation method comprises the following steps:

[0020] Mixing silicon powder and diluent in proportion to obtain mixed powder;

[0021] The mixed powder is loosely loaded into the substrate of the reaction material frame with a loading thickness of 4-6 cm, and a self-propagating combustion synthesis reaction is carried out in a nitrogen atmosphere to obtain α-phase silicon nitride ceramic powder.

[0022] Furthermore, in the mixed powder, the silicon powder accounts for 30-45wt%, the diluent accounts for 55-70wt%, and the total mass percentage of the silicon powder and the diluent is 100wt%.

[0023] Furthermore, the diluent is selected from silicon nitride powder with an α-phase content greater than 80 wt%.

[0024] Furthermore, the maximum temperature of the self-propagating combustion synthesis reaction is 1600-1750° C., and the reaction time is 30-40 minutes.

[0025] Furthermore, the vertical distance from the lowest point of the reaction material frame to the upper surface of the reaction material is recorded as the charging thickness.

[0026] Furthermore, after the reaction material is paved, the vertical distance between the surface of the reaction material and the wave crest or the maximum height of the sawtooth shape is 1-5 cm, that is, the reaction material is 1-5 cm below the highest position of the substrate when paving.

[0027] Furthermore, when the self-developed reaction material frame of the present invention is used for preparation, the maximum combustion temperature in the reaction process can be reduced, wherein the maximum combustion temperature is measured using a paperless recorder. After summarizing a large amount of experimental data and fitting through the origin software, it is found that the maximum combustion temperature and the maximum height and width of the circulation unit satisfy the following relationship: T≤1850-30h-20l, wherein T is the maximum combustion temperature, in °C; h is the maximum height of each circulation unit (the height at the wave crest or the maximum height of the sawtooth), in cm; l is the width of each circulation unit (the wavelength or the bottom length), in cm.

[0028] Furthermore, when the self-developed reaction material frame of the present invention is used for preparation, the content of α-phase silicon nitride can be increased compared with the flat-bottomed material frame. After a large amount of experimental data is summarized and fitted by the origin software, it is found that the α content and the maximum height and width of the cycle unit satisfy the following relationship: a>2.5(h+l), and a is not greater than 30%. Wherein, a is the increase in α-phase silicon nitride, in wt%; h is the maximum height of each cycle unit (the height at the wave crest or the maximum height of the sawtooth), in cm; l is the width of each cycle unit (wavelength or bottom side length), in cm.

[0029] In order to achieve the third object, the present invention adopts the following technical solutions:

[0030] The present invention discloses an α-phase silicon nitride ceramic powder prepared by the above-mentioned preparation method, wherein the α-phase content of the α-phase silicon nitride ceramic powder is greater than 80wt%.

[0031] The beneficial effects of the present invention are as follows:

[0032] The invention discloses a reaction material frame with periodically changing paving thickness. The reaction material frame has a special shape design in the substrate part, which is changed from the traditional flat bottom design to a shape with periodic shape change. Through these regular convex designs, the paving thickness of the reaction material can be periodically changed, the contact area between the reaction material and the reaction material frame is increased during paving, the problem of uneven heat dissipation of the reaction material during the combustion process is improved, and the heat dissipation efficiency of the reaction material is improved.

[0033] The present invention also discloses a method for preparing α-phase silicon nitride ceramic powder. The self-developed and designed reaction material frame is used to reduce the maximum reaction temperature in the self-propagating combustion synthesis process, increase the heat dissipation efficiency, reduce the local overheating phenomenon, and increase the yield of α-phase silicon nitride by more than 7%. The α-phase silicon nitride content in the synthetic product is greater than 80wt%. At the same time, the preparation method also has the advantages of simple operation, simple control, strong feasibility, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings.

[0035] Figure 1 A schematic diagram of a reaction frame with a corrugated substrate is shown.

[0036] Figure 2 A schematic diagram of the reaction material frame after adding the mixed powder is shown. DETAILED DESCRIPTION

[0037] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0038] The present invention provides a reaction material frame for periodically changing the thickness of a paving material, the reaction material frame comprising an upper structure and a lower structure; the upper structure and the lower structure are integrally formed;

[0039] The upper structure of the reaction material frame adopts a conventional reaction material frame design, the upper structure is a rectangular parallelepiped frame with a lower opening, and the lower structure of the reaction material frame is a substrate with a periodically changing shape.

[0040] Furthermore, the substrate has a wavy shape, and each circulation unit is a semi-ellipsoidal shape with the same size. Different wavy material frames can be designed by changing the wavelength (denoted as l) or the peak (denoted as h) size of each wavy circulation unit.

[0041] Furthermore, the vertical distance between the wave crest and the upper structure is 6 cm.

[0042] Furthermore, the overall size of the reaction material frame is 20×10×8 cm.

[0043] Furthermore, the reaction material frame is made of stainless steel.

[0044] Example 1

[0045] According to the mass percentage of 40wt% silicon powder and 60wt% diluent, the ingredients were prepared and mixed to obtain a uniform mixed powder, totaling 200g. The mixed powder was placed in a wavy material frame (h is 1cm, l is 2cm). After spreading, the reaction material was 3cm above the wave peak. Then, the wavy material frame was placed in a reactor and a self-propagating combustion synthesis reaction was carried out in a 4MPa nitrogen atmosphere. The reaction lasted for 35min, during which the highest combustion temperature was 1763°C. After the reaction, a product powder was obtained. The product powder was characterized by XRD, and the α phase content was 81%.

[0046] Example 2

[0047] According to the mass percentage of 40wt% silicon powder and 60wt% diluent, the ingredients were prepared and mixed to obtain a uniform mixed powder, totaling 200g. The mixed powder was placed in a wavy material frame (h is 3cm, l is 5cm). After spreading the materials, the reaction materials covered the wave peaks by 5cm. Then, the wavy material frame was placed in a reactor and a self-propagating combustion synthesis reaction was carried out in a 4MPa nitrogen atmosphere. The reaction lasted for 30min, during which the highest reaction temperature was 1633°C. After the reaction, a product powder was obtained. The product powder was characterized by XRD, and the α phase content was 91%.

[0048] Example 3

[0049] According to the mass percentage of 40wt% silicon powder and 60wt% diluent, the ingredients were prepared and mixed to obtain a uniform mixed powder, totaling 200g. The mixed powder was placed in a wavy material frame (h is 1cm, l is 5cm). After spreading, the reaction material was 4.3cm above the wave peak. Then, the wavy material frame was placed in a reactor and a self-propagating combustion synthesis reaction was carried out in a 4MPa nitrogen atmosphere. The reaction lasted for 34min, during which the highest reaction temperature was 1702°C. After the reaction, a product powder was obtained. The product powder was characterized by XRD, and the α phase content was 85%.

[0050] Example 4

[0051] According to the mass percentage of 40wt% silicon powder and 60wt% diluent, the ingredients were prepared and mixed to obtain a uniform mixed powder, totaling 200g. The mixed powder was placed in a wavy material frame (h is 3cm, l is 2cm). After spreading, the reaction material submerged the wave peak by 4.5cm. Then, the wavy material frame was placed in a reactor, and a self-propagating combustion synthesis reaction was carried out in a 4MPa nitrogen atmosphere. The reaction time was 36min, and the maximum reaction temperature during the reaction was 1694°C. After the reaction, a product powder was obtained. The product powder was characterized by XRD, and the α phase content was 87%.

[0052] Example 5

[0053] According to the mass percentage of 30wt% silicon powder and 70wt% diluent, the ingredients were prepared and mixed to obtain a uniform mixed powder, totaling 200g. The mixed powder was placed in a wavy material frame (h is 3cm, l is 2cm). After spreading, the reaction material covered the wave peak by 4cm. Then, the wavy material frame was placed in a reactor, and a self-propagating combustion synthesis reaction was carried out in a nitrogen atmosphere of 4MPa. The reaction time was 31min, and the maximum reaction temperature during the reaction was 1634°C. After the reaction, a product powder was obtained. The product powder was characterized by XRD, and the α phase content was 94%.

[0054] Comparative Example 1

[0055] This comparative example uses a conventional flat-bottomed frame for a propagating combustion synthesis reaction. The overall size of the flat-bottomed frame is the same as that of the wavy frame used in the example, and the only difference is the shape of the substrate.

[0056] According to the mass percentage of 40wt% silicon powder and 60wt% diluent, the ingredients were prepared and mixed to obtain a uniform mixed powder, totaling 200g. The mixed powder was placed in a flat-bottomed material frame. After spreading, the thickness of the reaction material was 3.5cm. The flat-bottomed material frame was then placed in a reactor, and a self-propagating combustion synthesis reaction was carried out under a 4MPa nitrogen atmosphere. The reaction time was 39min, during which the maximum reaction temperature was 1837°C. After the reaction was completed, a product powder was obtained. The product powder was characterized by XRD, and the α phase content was 69%.

[0057] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A reaction material frame for periodically changing the thickness of the material, characterized in that: The reaction material frame comprises an upper structure and a lower structure; the upper structure and the lower structure are integrally formed; Wherein, the lower structure of the reaction material frame is a substrate whose outer shape changes periodically.

2. The reaction material frame according to claim 1, characterized in that: The outer shape of the substrate includes one or both of a wave shape and a sawtooth shape.

3. The reaction material frame according to claim 1, characterized in that: When the substrate has a wavy shape, the wavelength of each wavy cycle unit is 2-5 cm, the peak height of each wavy cycle unit is 1-3 cm, and the vertical distance between the peak and the upper structure is 5-7 cm.

4. The reaction material frame according to claim 1, characterized in that: When the substrate has a sawtooth shape, the bottom side length of each sawtooth circulation unit is 2-5 cm, the maximum height of each sawtooth circulation unit is 1-3 cm, and the vertical distance between the maximum height of each circulation unit and the upper structure is 5-7 cm.

5. The reaction material frame according to claim 1, characterized in that: The material of the reaction frame includes stainless steel or graphite.

6. A method for preparing α-phase silicon nitride ceramic powder, characterized in that: Utilizing the reaction frame as described in any one of claims 1 to 5, α-phase silicon nitride ceramic powder is prepared by self-propagating combustion synthesis method.

7. The method according to claim 6, characterized in that The preparation method comprises the following steps: Mixing silicon powder and diluent in proportion to obtain mixed powder; The mixed powder is loosely loaded into the substrate of the reaction material frame with a loading thickness of 4-6 cm, and a self-propagating combustion synthesis reaction is carried out in a nitrogen atmosphere to obtain α-phase silicon nitride ceramic powder.

8. The method according to claim 7, characterized in that In the mixed powder, the silicon powder accounts for 30-45wt%, the diluent accounts for 55-70wt%, and the total mass percentage of the silicon powder and the diluent is 100wt%; Preferably, the diluent is selected from silicon nitride powder with an α-phase content greater than 80 wt%.

9. The method according to claim 7, characterized in that: The maximum temperature of the self-propagating combustion synthesis reaction is 1600-1750° C., and the reaction time is 30-40 minutes.

10. The α-phase silicon nitride ceramic powder prepared by the method according to any one of claims 6 to 9, characterized in that: The α-phase content of the α-phase silicon nitride ceramic powder is greater than 80 wt %.

Citation Information

Patent Citations

  • A method for preparing α-phase silicon nitride ceramic powder

    CN110256084B